Schottky's barrier height of T91/Cr2O3 heterojunction in dry and wet conditions: effects of watervapor onto accelerated high temperature oxidation - Ani, Mohd Hanafi; Zaharudin, M Z; ., Suryanto; Purwanto, Hadi; Din, M.F.M.; ., T. Kurniawan (IEEE, 2018)
Increasing the operating temperature in thermal power plant will further accelerate the high temperature oxidation with the presence of water vapor. It is hypothesized that water vapor provides hydrogen that dissolves into the ferritic alloy susbstrate, hence altering their electronic state at the metal-semiconductor (oxide) interface. This study aims to quantitatively prove above postulation by comparing their Schottky's Barrier Height (SBH) in dry and wet environment. The Schottky's barrier was prepared by sputtering Cr2O3 onto the T91 boiler tube in high vacuum condition using RF power 150W for an hour. The T91/Cr2O3 junction was then connected with platinum wire for capacitance-voltage, C-V test at high temperature. The value of Vbi was used to calculate the SBH, which increase proportionately with built in voltage. It is clearly shown that the SBH value in wet condition is higher than that in dry condition by 10.3%. This is explained by the formation of space charge layer at metal/oxide interface due to dissolved hydrogen in metal, thus may change the transport property and accelerate the oxidation rate in water vapor.